A new view of language, emotion and the brain - Shanahan, Daniel (Integrative psychological & behavioral science, 2008)
Linguistic theory since the Cognitive Revolution has followed one of the premises of that revolution by largely sidelining the issue of emotions and concentrating on those aspects of language that are more strictly cognitive. However, during the last two decades research in cognitive science, especially in neuropsychology, has begun to fill in the gaps left by the exclusion of emotions from cognitive research. This article proposes a model for applying the fruits of this new research in emotion to our understanding of language itself. Building on Karl Pribram's integrated model of emotions and motivations, the presentation it offers a propositional explanation for how the emotions may have contributed to the emergence of symbolic formation and, ultimately, to every aspect of language from lexis to literature.
Keywords: Animals; Emotions; Models, Psychological; vědomí; Consciousness; emoce; symbolismus; lidé; Symbolism; jazyk (prostředek komunikace); mozek; psychologická teorie; Psycholinguistics; Brain; psychologické modely; Psychological Theory; Language; psycholingvistika; zvířata; Humans